Effective mass persuasion medium for political campaign: the impact of photographic images in newspapers on the public during general election 11th (2004) and general election 12th (2008) / Md Nagib Padil - Padil, Md Nagib (2019)
During the General Election is approaching in Malaysia, the photos being featured in the local newspapers are one of the most important elements that is used to gain the public votes. The newspapers use the medium of photography to report the latest progress of the parties taking part in the general election and the activities that are going on throughout the campaign. However, during the 11th General Election in 2004 and the 12th General Election in 2008, there were pictures being published in the local Malaysian newspapers that were complained by the general public. The frequency of the local newspapers publishing pictures that showed inclination towards a certain political party had caused various critics and had also tarnished the trust of the public towards the news being published by the local newspapers until there were evidence that during the 12th General Election the general public were more inclined to refer and seek for information from the internet and blogs. As a result, this study is conducted to compare the use of pictures which were used in the selected local newspapers in reporting the news during the two general elections, 11th and 12th and study the perceptions of the general public of the impacts of the pictures in the news reported during the campaigns. In insuring that the objectives of this research are achieved, a qualitative approaches like interview, questionnaire and content analysis are applied to gather the data for this study. The findings suggest that throughout the duration of the campaign the majority of the photos of the campaigns which were used to report the news by the selected local newspapers were still showing inclination towards a certain political parties as sources of reference for the readers. The majority of the photos used in the articles reported during the two general elections were just to show the heated battle between the two main parties participating in the general election which were Barisan Nasional (BN) and Pakatan Alternatif. Even though the photos of the campaigns used in reporting the news of the two general elections were interesting and used unique presentation techniques, the photos used did not actually convey the current issues and were not parallel with the interests of the readers, as well as did not actually influence their emotions who viewed them, especially during the 12th General Election.